The perceptibility of mistuned melodic intervals by school children - HARAJDA, H.; FYK, J. (Archives of Acoustics, 1981)
The aim of this study was to investigate the perceptibility of detuned (mistuned) melodic intervals of prime (1), minor second (2m), major second (2w) and minor third by school children, depending on the sound timbre and the age of persons examined. The investigation included isolated intervals and intervals in a melodic context. The results obtained for age groups from different centres were compared. It was found that a student of average musical talent tends to perceive detuned melodic intervals below a quarter tone. The perceptibility of these detunings is much higher in intervals composed of musical sounds ("coloured" sounds) occurring in a musical context than in isolated intervals composed of sinusoidal tones. The age of a student or the centre from which he comes were found not to have an effect on the perceptibility of the detunings.